Enhanced expression of CD39 and CD73 on T cells in the regulation of anti-tumor immune responses - Shevchenko, Ivan; Mathes, Andreas; Groth, Christopher; Karakhanova, Svetlana; Müller-Bütow, Verena; Utikal, Jochen; Werner, Jens; Bazhin, Alexandr V.; Umansky, Viktor (OncoImmunology, 2020)
Synthesis of extracellular adenosine by the ectonucleotidases CD39 and CD73 represents an important pathway of immune suppression in the tumor microenvironment. Using two mouse models (RET transgenic melanoma and Panc02 orthotopic pancreatic adenocarcinoma), we identified an elevated frequency of ectonucleotidase-expressing T cells in tumors and spleens. Importantly, these ectonucleotidase-positive T cells also showed a pronounced expression of PD-1. Conversely, the PD-1+ T cell subsets in tumors contained substantially larger proportions of ectonucleotidase-expressing cells compared to their counterparts lacking PD-1 expression. Our in vitro experiments showed that the activation of normal T cells resulted in an increase in the CD39 expression. CD39+ and CD73+ T cells displayed effector or memory phenotypes and produced IFN-γ, thereby linking ectonucleotidase expression to T cell effector functions. An accumulation of conventional and regulatory T cells expressing CD39 and/or CD73 was also detected in the peripheral blood of patients with melanoma and pancreatic cancer. Moreover, we demonstrated a significant association between low frequencies of circulating CD73+CD8+ T cells and CD73+CD4+ regulatory T cells and better overall survival of melanoma patients. Tumor-derived soluble factors (in particular, TGF-β) significantly enhanced the frequencies of ectonucleotidase-expressing cells in mice. Our findings suggest that the upregulation of ectonucleotidase expression in T cells promotes extracellular adenosine accumulation and represents an important mechanism of homeostatic immune auto-regulation, which could be hijacked by tumors to evade anti-cancer immunity. Targeting CD39 and CD73 can open new avenues for cancer immunotherapy.